2016
DOI: 10.1097/dcr.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Rectal Adenocarcinoma Is Associated with a Poor Response to Neoadjuvant Chemoradiotherapy: A Systematic Review and Meta-analysis

Abstract: Mucinous rectal adenocarcinoma represents a biomarker for poor response to preoperative chemoradiotherapy and is an adverse prognostic indicator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
97
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 30 publications
9
97
0
6
Order By: Relevance
“…This difference in cutoff value may explain the higher incidence of MA in the western countries compared to those in Asia [16,19]. Many studies showed that patients with MA of the rectum had worse prognosis in terms of RFS and OS compared to non-mucinous adenocarcinoma (NMA) [9,19,20]. On the other hand, the prognostic significance of MA of the colon is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in cutoff value may explain the higher incidence of MA in the western countries compared to those in Asia [16,19]. Many studies showed that patients with MA of the rectum had worse prognosis in terms of RFS and OS compared to non-mucinous adenocarcinoma (NMA) [9,19,20]. On the other hand, the prognostic significance of MA of the colon is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some pathological features have been shown to predict the response to nCRT. Tumor differentiation, circumferential tumor, mucinous histology and the presence of macroscopic ulceration are associated with poor response to nCRT [20,21,22,23,24]. Imaging modalities including positron emission tomography-computed tomography, magnetic resonance imaging (MRI) and endoscopic ultrasound are currently used for pretreatment staging, assessment of response to nCRT, and restaging after nCRT [25,26,27,28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Clinicopathological factors associated with the CRT response to rectal cancer include the levels of serum carcinoembryonic antigen (CEA), carbohydrate antigen 19-9, and fibrinogen; the histological grade and mucinous histology; tumor size, volume, circumference, and movability; the hemoglobin level and blood lymphocyte counts; the clinical T or N stage; and the distance from the tumor to the anal verge [21,[45][46][47][48][49][50][51][52][53][54][55][56][57]. Of these factors, the serum CEA level has been the most relevant [48][49][50].…”
Section: Predictive Markers Clinicopathological Factorsmentioning
confidence: 99%